North Jamrud Terminal Warehouse Performance by The Effect of Halal Logistics Issue - Ingsih, Ita Suhermin; Arifin, M. Zainul; Wicaksono, Achmad (Fakultas Teknik UB, 2018)
The Government today, Government Business Entity and mass media in Indonesia are starting to pay attention to halal, since the turnover of halal products of the world has reached nearly 2 trillion dollars while Indonesia is still larger to be a consumer than a manufacturer. Not only foods, consumers in the world today want cosmetics to pharmaceutical products that have been halal certified. In Indonesia, problems with the potential of halal market today are still hit on the discourses. Indonesia still limited awareness not yet dared to action, whereas in nonMuslim countries themselves many have implemented halal supply chain. The establishment of Halal Hub Port in Tanjung Priok as the first Halal Hub Port pilot project in Indonesia is the forerunner to establish Halal Hub Port in other parts of Indonesia. Therefore, it is necessary to examine the needs of Halal Warehouse at Tanjung Perak Port which in fact is also a major port in Indonesia and is a distribution door for the central and eastern part of Indonesia. The study was conducted on 190 respondents who are stakeholders of Tanjung Perak Port. Using the Importance Performance Analysis method, the results of the research produced a quadrant graph where quadrant A is the main priority containing performance of L/U equipment in terminal, performance of L/U workers/operator in terminal, separation of halal and non-halal products in halal warehouse, sorting of halal and non-halal products that have been damaged, cold storage separation between halal and non-halal products, clean and avoid contamination between products, special training for officers in halal warehouse, and hygiene facilities for officers in warehouse/halal warehouse. Quadrant B is to maintain the achievement contains 11 items, Quadrant C is low priority contains 5 items, and Quadrant D is excessive contains 5 items. The existence of 8 items entered in quadrant A, indicating that stakeholders at Tanjung Perak Port are very aware with the potential of Halal Warehouse.